Tutorial Pemanfaatan Konten Gambar Promosi Produk Melalui Aplikasi Canva di Kelurahan Sendanggowa Semarang - Scorina Dwiantari; Irene Nathalia Setiawan; Hendra Wijaya (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Background of this Community Service MSME actors in Sendangguwo Village lack knowledge and understanding of the importance of using product promotion media through digital marketing and attractive design for image content. Partners have been operating for quite a long time by using social media only using WhatsApp and using very simple product image designs, so they do not attract enough consumers. The expected results and outputs of Community Service to MSME partners in Sendangguwo Village are being able to apply knowledge about product promotion through several digital marketing, gaining the ability to operate the Canva application using android, gaining the ability to create several image content designs for product promotion e-catalogs, so that partners no longer have difficulty creating product promotion image content designs to be uploaded to digital marketing.